Clinical features and short-term outcomes of pediatric acute fulminant myocarditis in a single center - Eun Young Lee; Hae Lyoung Lee; Hyung Tae Kim; Hyoung Doo Lee; Ji Ae Park (Korean Pediatric Society, 2014)
PurposeThe aims of this study were to document our single-center experience with pediatric acute fulminant myocarditis (AFM) and to investigate its clinical features and short-term outcomes.MethodsWe performed a retrospective chart review of all children <18 years old who were diagnosed with AFM between October 2008 and February 2013. Data about patient demographics, initial symptoms, investigation results, management, and outcomes between survivors and nonsurvivors were collected.ResultsSeventeen of 21 patients (80.9%) with myocarditis were diagnosed with AFM. Eleven patients (64.7%) survived to discharge, and 6 (35.3%) died. Electrocardiography on admission revealed dysrhythmia in 10 patients (58.8%); of these, all 7 patients with a complete atrioventricular block survived. Fractional shortening upon admission was significantly different between the survivors (16%) and nonsurvivors (8.5%) (P=0.01). Of the serial biochemical markers, only the initial brain natriuretic peptide (P=0.03) and peak blood urea nitrogen levels (P=0.02) were significantly different. Of 17 patients, 4 (23.5%) required medical treatment only. Extracorporeal membrane oxygenation (ECMO) was performed in 13 patients (76.5%); the survival rate in these patients was 53.8%. ECMO support was initiated >24 hours after admission in 4 of the 13 patients (30.7%), and 3 of those 4 patients (75%) died.ConclusionAFM outcomes may be associated with complete atrioventricular block upon hospital admission, left ventricular fractional shortening at admission, time from admission to the initiation of ECMO support, initial brain natriuretic peptide level, and peak blood urea nitrogen level.